2004
DOI: 10.1128/jcm.42.4.1477-1482.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multidrug-Resistant Typhoid Outbreaks in Kenya

Abstract: We characterized by antibiotic susceptibility, plasmid analysis, incompatibility grouping, and pulsed-field gel electrophoresis (PFGE) of XbaI-and SpeI-digested DNA 102 Salmonella enterica serovar Typhi (serovar Typhi) isolated from recent outbreaks of typhoid in three different parts of Kenya. Only 13.7% were fully susceptible, whereas another 82.4% were resistant to each of the five commonly available drugs: ampicillin, chloramphenicol, and tetracycline (MICs of >256 g/ml); streptomycin (MIC, >1,024 g/ml); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 29 publications
5
66
1
1
Order By: Relevance
“…Since the first report of MDR serovar Typhi outbreaks, which occurred in Kenya in 1997 to 1999 [18] when the prevalence of the MDR phenotype was 50 to 65%, our current hospital-based surveillance has shown that only 13.7% isolates were fully susceptible to all drugs tested, while 75-82% of S. Typhi from blood cultures and CSF are MDR with particularly high MICs of ampicillin, chloramphenicol, tetracycline, (MICs > 256µg/ml), streptomycin (MIC > 1024µg/ml) and cotrimoxazole (MIC> 32µg/ml) [7]. In all the isolates showing this multidrug resistance phenotype, a self-transferable large plasmid approximately 110 kb of incompatibility group HI1 was associated with encoding the resistance.…”
Section: J Infect Developing Countriesmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the first report of MDR serovar Typhi outbreaks, which occurred in Kenya in 1997 to 1999 [18] when the prevalence of the MDR phenotype was 50 to 65%, our current hospital-based surveillance has shown that only 13.7% isolates were fully susceptible to all drugs tested, while 75-82% of S. Typhi from blood cultures and CSF are MDR with particularly high MICs of ampicillin, chloramphenicol, tetracycline, (MICs > 256µg/ml), streptomycin (MIC > 1024µg/ml) and cotrimoxazole (MIC> 32µg/ml) [7]. In all the isolates showing this multidrug resistance phenotype, a self-transferable large plasmid approximately 110 kb of incompatibility group HI1 was associated with encoding the resistance.…”
Section: J Infect Developing Countriesmentioning
confidence: 97%
“…A breakdown in the portable water system in a South African suburb caused an outbreak of typhoid , causing illness in nearly 4,000 persons as well as several deaths [6]. In Kenya, multidrug-resistant (MDR) S. Typhi strains in adults and school-age children were previously associated with sporadic outbreaks in resource-poor settings [7].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple antibioticresistant strains for primary drugs (ampicillin, chloramphenicol, co-trimoxazole and tetracycline) have been reported in many countries (4,10,15,17,19). In this study, isolated strains were mostly sensitive with no ESBL ones.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium is endemic in many parts of world causing typhoid fever (2,4,7,11,18). Typhoid fever is a severe and life-threatening systemic illness transmitted via the fecal-oral route and is a major cause of morbidity and mortality worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Chandel e Chaudhry (2) encontraram um único clone entre amostras de S. Typhi isoladas na Índia durante cinco anos. Outros autores, como Kariuki et al (8) , também relataram a presença de um surto de febre tifóide no Quênia; já Thong et al (20) observaram aumento da diversidade genética de isolados de S. Typhi na Nova Guiné de 1992 a 1999.…”
Section: Eletroforese Em Gel De Campo Pulsadounclassified